alguém me ajuda por favor
Anexos:
![](https://pt-static.z-dn.net/files/df9/999fefc29969595cb530d997f249971e.jpg)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
f(-2) = - 3. (-2) - 3 = + 6 - 3 = + 6 - 3 = 3 (-2, 3)
f(-1) = - 3. (-1) - 3 = + 3 - 3 = + 3 - 3 = 0 (-1, 0)
f(0) = - 3.0 - 3 = + 0 - 3 = + 0 - 3 = -3 (0, -3)
Anexos:
![](https://pt-static.z-dn.net/files/df5/714fd1beacac251d2498aafe3954dec6.jpg)
andradejp451529:
obrigado
Perguntas interessantes
Português,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
1 ano atrás